From Logic to Nature: Hegel’s Post-Kantian Non-Romantic Naturphilosophie (Revista Eletrônica Estudos Hegelianos, 2024)
This is to lay out the issues involved in an appropriately post-Kantian interpretation of Hegel’s Naturphilosophie, which I translate not as “philosophy of nature” but as “natural philosophy”. Pure thought as Kant argued is empty, but he thought that he could supply pure content to it by the combination of pure intuitions and the unity of self-consciousness. His successors, especially Fichte, did not think that resolved matters, and Hegel tried to make good on what he saw as the failures of Fichte’s attempt to do Kantian philosophy without pure intuitions. Hegel however also saw that one could not begin with self-consciousness per se or with Fichte’s “I.” Instead, Hegel proposed a Logic that would give an internally self-enclosed system of pure thoughts as what was needed to make sense of making sense. Famously, he concluded the system with some not entirely clear ideas about its needing a move to a Naturphilosophie that was not a move in terms of a “transition.” Pure thought thus developed a concept of that which would be external to pure thought itself (like Fichte’s “Not-I”) but still something intrinsically linked to pure thought. This is the very concept of “externality to pure thought itself,” which first appears as space and time. The development of the simple thought of “external to pure thought” leads to a non-empiricist account of nature. Empiricists study regularities of nature in the Humean sense, but these regularities, although existent, are not fully “actual” in that they are not what is doing the work of explanation. What explains the regularities themselves are the various pure objects of the Naturphilosophie: The mechanical, the physical, the chemical and the biological fields of nature, each of which manifests a power [Potenz] that explains why the empirically found regularities in nature actually hold. The basic objects of a true Naturphilosophie present a unified field of investigation that is defined by the field’s powers and which in turn calls out for an empirical investigation of how these powers actually operate in the vast continuum of nature. Each of these distinct fields moreover has its own distinct form of causality, culminating in the causality of freedom in the human realm. It is then suggested that the reason for the transition from Logic to Nature is that pure thought on its own is powerless and finds itself filled with only the shadows of the world as a whole. This has implications for how we think of Hegel’s system as a whole.